Generalizing the Design of PAT Hydropower Plants in Water Networks - Djordje Mitrovic; Prysor Williams; Aonghus McNabola (Environmental Sciences Proceedings, 2022)
Coupling pressure management strategies with energy generation in water distribution networks could provide an opportunity to reduce energy dependency. Recent laboratory prototypes attested the capability of Pump-As-Turbines (PATs) to manage pressure and generate energy in these settings. When selecting an optimal pump/PAT unit from the market to maximize energy recovery at a Pressure Reduction Valve (PRV) site, the first step usually represents the definition of its optimal design point in turbine mode, i.e., its best efficiency point (BEP) for a selected rotational speed. There are many very different strategies on how to define the optimal design point of PATs, and by far the simplest is to define it as the average operating condition (AOC) at an investigated site. However, the literature does not provide the answer if such a definition is valid. More importantly, of whether it is valid for a general case, meaning regardless of the site’s size, level of variations of operating conditions and other site-specific characteristics. To address this research question, a large database of high-resolution recordings from 38 PRVs was compiled. The optimal design point for each PRV was assessed using an upgraded version of a methodology from the literature employing the Nelder–Mead Simplex Direct Search algorithm and hydraulic control strategy. The upgrade includes the addition of a new design variable representing the maximal operating flow of the PAT. The optimization of this variable also results in the optimization of the size of the generator. The results suggest that the selection of the optimal PAT from the market using the AOC could lead to the selection of the same models as when using the true theoretical optimal design point in the case of 77.14% of the investigated sites. Furthermore, the PAT models selected using the AOCs of the investigated sites were at least the second optimal for 99.14% of sites. Consequently, it was concluded that, for practical purposes (i.e., when a PAT database is not available and the optimal model is found from pump selection charts), it is appropriate to use the AOCs of the investigated site for the selection.